Nickel coated flyash (Ni-FAC) cenosphere doped polyaniline composite film for electromagnetic shielding. (6th March 2015) - Bora, Pritom J; Vinoy, K J; Ramamurthy, Praveen C; Kishore,; Madras, Giridhar
Abstract: A solid waste material fly ash cenosphere (FAC) was nickel coated and polyaniline in situ polymerized at −30 ± 2 °C in nitrogen atmosphere. A thin film of this composite material was prepared by solution processing and surface morphology/topography was studied. High electromagnetic shielding effectiveness (SE) was obtained for this film; 59 ± 4 μ m and 133 ± 4 μ m films show an average of 38 and 60 dB SE, respectively, in the frequency range 8.2–12.4 GHz (X-band). Unlike PANI film, the SE of these composite films is high at high frequency. The presence of magneto dielectric microsphere (Ni-FAC) increases the heterogeneity of the composite film in an efficient way for EMI shielding by changing film topography and increasing ac conductivity and permeability.